STOMACH CONTENTS OF MNEMIOPSIS LEIDYI IN THE IRANIAN COASTAL WATERS OF THE CASPIAN SEA - S. Bagheri; J. Sabkara (‬‭Majallah-i ̒Ilmī-i Shīlāt-i Īrān, 2003)
This study was carried out from August to November 2002 in the Iranian coastal waters of the Caspian Sea (Guilan province). The results showed that gut contents of Mnemiopsis leidyi included a wide variety of prey including 84% of zooplanktons and 16% of phytoplanktons. The most abundance of intaked foods was Acartia (belongs to Copepoda) with 34% frequency and the least was podon (belongs to Cladocera) with 0.74% frequency. Also 3.0% of fish eggs and 4.2% of molluscs were found among stomach contents. Maximum and minimum fed phytoplanktons were Chrysophyta (67.0%) and Pyrrophyta (3.7%), respectively. The young specimen consumed more zooplanktons and phytoplanktons comparing to adult ones. According to laboratory observations, this ctenophore cannot digest phytoplanktons.